Secure Bootstrapping and Rebootstrapping for Resource-Constrained Thing in Internet of Things - Seung Wook Jung; Souhwan Jung (International Journal of Distributed Sensor Networks)
In Internet of Things, secure key establishment and building trust relationship between the thing and the home gateway (or the controller) in home network or Body Area Network are extremely important. Without the guarantee of establishment of key and trust relationship, the traffic over the Internet of Things network cannot be presumed secure. Also, when the home gateway, which knows the shared secret key, is out of order and the new gateway should be installed, the secure key establishment and building trust relationship are also very important because this scenario is likely to happen in real world. In addition, the thing is resource-constrained device, so it is difficult when secure key establishment and building trust relationship involve Public Key Infrastructure. To address these problems, this paper presents user-friendly bootstrapping and rebootstrapping schemes in the context of Internet of Thing using the human memorable password. The proposed schemes do not require a special hardware module on the thing or special equipment for bootstrapping and rebootstrapping. All these properties make the proposed scheme cost-effective and easy to use.